Gender stereotypes in physical education - Pastor-Vicedo, JC.; Sánchez-Oliva, A.; Sánchez-Blanchart, J.; Martínez-Martínez, J. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
The school, and the Physical Education may become as one of the setting where with the so-called hidden curriculum, attitudes loaded with prejudices, in terms of gender stereotyped, could be shown. The main objective of our study was to identify the perception of primary school students between 11 and 12 years old (11.87 ± 0.38) about gender stereotypes linked to physical activity and sport, based on sub-stereotypes associated with the type of practice , regarding the teaching staff and classroom climate. The main results show the presence of stereotypes related to performance, self-concept and treatment by teachers. From the school and from the area of Physical Education, we must bear in mind these situations that we must reorient to achieve a true inclusive school and society that allows equal opportunities.